Ergonomic Risk Assessment of Warehouse Workers in the Courier Service Industry: A Case Study from Kuantan, Malaysia - Alya Nadhirah binti Ismail; Mirta Widia; Ezrin Hani binti Sukadarin; Wan Norlinda Roshana Binti Mohd Nawi; Mohammad Faizal bin Zainal Abidin (Jurnal Optimasi Sistem Industri, 2024)
The global surge in demand for courier services has introduced both benefits and challenges. Courier workers face immense pressure to handle large volumes of orders, leading to increasing cases of health and occupational injuries. The lack of ergonomic interventions in their work highlights the urgent need for ergonomic assessments in the courier industry. In Malaysia, current ergonomic risk assessments for warehouse courier workers are insufficient, making it essential to identify prevalent musculoskeletal disorders (MSDs) and determine the associated risk factors and levels posed by their daily tasks. This study aimed to address this gap by conducting ergonomic risk assessments among 35 warehouse workers using the Cornell Musculoskeletal Discomfort Questionnaire (CMDQ), the Initial Ergonomic Risk Assessment (ERA) Checklist, and Rapid Entire Body Assessment (REBA). Three different work tasks were observed: scanning and sorting, tiered storage and stacking, and load unloading. The findings revealed that lower back pain was the most common ailment (14.5%), followed by hip pain (8.39%) and neck pain (7.89%). The tiered stacking storage activity posed the highest ergonomic risk, with identified risk factors including awkward postures, static and sustained activity, and repetitive tasks. The REBA analysis indicated a very high-level risk for tiered stacking storage, necessitating immediate ergonomic interventions. These findings contribute to the field of ergonomics and provide valuable insights for safety practitioners, ergonomists, researchers, and academicians in occupational safety and health and the courier service industries.